Nanothin Descemet stripping automated endothelial keratoplasty performed on a lacerated cornea after globe rupture: a case report - Shin-ichiro Ito; Takahiro Nakamura; Daiki Sakai; Marika Hirota; Chie Sotozono; Yasuo Kurimoto (BMC Ophthalmology)
Abstract Background When performing corneal endothelial transplantation, the presence of low intraocular pressure, abnormal host corneal shape, and septal defects between the anterior and posterior chamber may cause poor graft adhesion. We report our experience with Descemet stripping automated endothelial keratoplasty (DSAEK) using a nanothin graft in a case of bullous keratopathy (BK) in a lacerated cornea after globe rupture—a situation that encompasses these risk factors. Case presentation An 81-year-old man was admitted to our department after he had ruptured his right eyeball following a fall. On the same day, he underwent sclerocorneal suturing, vitrectomy, and intraocular injection of silicone oil. Because the sclerocorneal laceration was healed and there was no recurrence of vitreous hemorrhage or retinal detachment, the silicone oil was removed, and intrascleral fixation of the intraocular lens was performed 2 months later. However, as BK progressed, DSAEK was performed. We observed low intraocular pressure (approximately 5 mmHg), an abnormal corneal shape, and a septum defect between the anterior and posterior chamber, which could cause poor graft adhesion. The nanothin graft (diameter, 7.75 mm; thickness, 47 μm) gradually developed poor adhesion near the corneal laceration on the temporal side postoperatively. However, during reoperation, the graft was eccentrically placed on the nasal side, and air injection into the anterior chamber was added, which ultimately made it possible to attach the graft without sutures. Visual acuity was 20/2000 preoperatively but was 20/200 3 months postoperatively. Conclusions We experienced a severe case of BK in lacerated cornea after globe rupture, wherein nanothin DSAEK was performed with graft reposition, and the graft adhered well to the host cornea, resulting in improved visual function.